Giants and Toys Based on a Novel by Takeshi Kaikô - Masumura, Yasuzo; Murai, Hiroshi; Kawaguchi, Hiroshi; Nozoe, Hitomi; Itô, Yûnosuke (Arrow Films, 2021)
"Giants and Toys" is a sharp and snappy corporate satire revolving around the ruthless machinations of a group of admen working in the confectionary industry. As a new recruit to the marketing department of World Caramel, fresh-faced graduate Nishi (Hiroshi Kawaguchi) is eager to impress his ambitious and hard-nosed boss Goda (Hideo Takamatsu), even if it strains his relationships with his college friend Yokoyama (Koichi Fujiyama) and budding love interest Masami (Michiko Ono), who work at the rival companies of Giant and Apollo. With Worlds lead over its competitors slipping badly, the two spot a chance to get back in the race in the shape of the pretty but unsophisticated 18-year-old, Kyoko (Hitomi Nozoe). Goda and Nishi get to work polishing this rough diamond as their new campaign girl, but as the three rival confectionary companies pitch themselves into an all-out advertising war that spills out onto the streets of Tokyo as it escalates to ludicrous extremes, Kyokos newfound fame starts going to her head. Making its worldwide Blu-ray debut, this lurid adaptation of the award-winning 1957 novel by Ken Kaiko is considered a landmark in Japanese film history and a key work by Yasuzo Masumura, one of the countrys most highly acclaimed directors of his generation. Its absurdist and acidly cynical take on the excesses of the media and advertising worlds recalls the work of Frank Tashlin, as it presents a garish vision of a bold new postwar Japan where traditional company values come head-to-head with American-style consumer capitalism. [Cover]